2022
DOI: 10.37637/ab.v5i2.953
|View full text |Cite
|
Sign up to set email alerts
|

Pangan dalam Kebun, Model Pertanian Petani Kepulauan: Analisis karakteristik lahan dan pendapatan petani Pulau Ternate

Abstract: Produksi pertanian terutama pangan dan hortikultura (sayur) oleh petani di Pulau Ternate menyesuaikan dengan ketersediaan lahan sesuai karakteristik kepulauan. Tujuan penelitian untuk mengidentifikasi karakteristik lahan dan jenis tanaman serta pendapatan budidaya tanaman pangan dan sayur dibawah tegakan tanaman perkebunan. Penelitian dilakukan di lapangan melalui pengamatan, wawancara dan kuesioner selanjutnya dilakukan analisis deskriptif untuk melihat peluang pengembangan usahatani.  Hasil penelitian menunj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…The results of the soil properties analysis, including soil water content at land and water capacity at permanent wilting point conditions for each land use on Hiri Island, showed that the level of water availability in the soil varied for each land use. These indicators of the physical properties of the soil, together with other chemical and biological properties of the soil, greatly influence the health and quality of the soil as a planting medium (Umasugi et al, 2022). Based on the analysis results presented in Notes: FC = field capacity; WP = permanent wilting point; dZ = effective depth; STo = soil moisture content.…”
Section: Water Availability Based On Land Usementioning
confidence: 99%
See 2 more Smart Citations
“…The results of the soil properties analysis, including soil water content at land and water capacity at permanent wilting point conditions for each land use on Hiri Island, showed that the level of water availability in the soil varied for each land use. These indicators of the physical properties of the soil, together with other chemical and biological properties of the soil, greatly influence the health and quality of the soil as a planting medium (Umasugi et al, 2022). Based on the analysis results presented in Notes: FC = field capacity; WP = permanent wilting point; dZ = effective depth; STo = soil moisture content.…”
Section: Water Availability Based On Land Usementioning
confidence: 99%
“…Apart from that, the types of farming crops, apart from being market-oriented, are also adapted to the culture of the local community (Saidani et al, 2022) as well as agricultural technology input, which aims to strengthen the local wisdom of the community, especially the knowledge of island farmers, thereby creating a balance between meeting economic needs and environmental sustainability, strengthening farmer institutions (Achmad et al, 2022). The study by Umasugi et al (2022) highlighted that plantation crops and farming of food crops and vegetables are characteristic of island areas, which are hilly and have a slightly sloping to sloping topography. This condition will increase farmers' ability to adapt to climate change and technological developments (Antwi-Agyei and Stringer, 2021) to achieve a sustainable agricultural system, with the main pioneers being island farmers (Ayu et al, 2020;Zollet and Maharjan, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to the potential production of rawit pepper, the yield of East Tidore farmers is still low. The problem is the capacity to cultivate land, planting on land with an inclination of >8%-30% as an island territory, thus limiting farmers ability to do cultivation [2]. Therefore, the principle of conservation must be applied to the land.…”
Section: Introductionmentioning
confidence: 99%